CoVeriTeam GUI: A No-Code Approach to Cooperative Software Verification - Lemberger, Thomas; Wachowitz, Henrik (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2024)
We present CoVeriTeam GUI, a No-Code web frontend to compose new software-verification workflows from existing analysis techniques. Verification approaches stopped relying on single techniques years ago, and instead combine selections that complement each other well. So far, such combinations were-under high implementation and maintenance cost-glued together with proprietary code. Now, CoVeriTeam GUI enables users to build new verification workflows without programming. Verification techniques can be combined through various composition operators in a drag-and-drop fashion directly in the browser, and an integration with a remote service allows to execute the built workflows with the click of a button. CoVeriTeam GUI is available open source under Apache 2.0: https://gitlab.com/sosy-lab/software/coveriteam-gui Demonstration video: https://youtu.be/oZoOARuIOuA